Effect of water temperature on egg incubation time and quality of newly hatched larvae of northern pike (Esox lucius L., 1758). (4th August 2015) - Bondarenko, V.; Drozd, B.; Policar, T.
Summary: This study examined the effect of temperature on egg incubation, survival of eggs during embryonic development and quality of newly hatched larvae of northern pike ( Esox lucius L.) under laboratory conditions. Eggs of similar size (diameter 2.7 ± 0.16 mm and weight 6.11 ± 0.35 mg) from five females were incubated at 3, 6, 10, 14, and 18°C (groups A, B, C, D, and E, respectively). The lowest fertilization (FR) and hatching rates (HR) were observed in larvae incubated in group A, 44.6 ± 3.2% and 18.26 ± 2.25%, respectively. The highest FR and HR were found in group B (FR, 71.3 ± 4.3%; HR, 56.2 ± 3.21%) and C (FR, 65.6 ± 3.1%; HR, 65.5 ± 5.41%). Time of incubation period varied from 38 ± 0.33 days (120 ± 1.03°d) when 5% larvae were hatched to 46 ± 0.42 days (144 ± 1.31°d) when 95% larvae were hatched in group A and 2.5 ± 0.08 days (44.67 ± 1.42°d) when 5% larvae were hatched to 3.42 ± 0.06 days (61.11 ± 1.07°d) when 95% larvae were hatched in group E. Larvae from groups A, D, and E were characterized by the lowest values of variables such as resistance to osmotic stress after 90 min of exposure of saline solution (OS = 54 ± 3–76 ± 3%), frequency of normally developed larvae (FNL = 23.8 ± 4.14–87. 1 ± 2.42%), and yolk sac volume (YsV = 3.41 ± 0.44–3.89 ± 0.45  μ l 3 ). The highest quality larvae were recorded in groups B and C: OS = 92 ± 3% and 80 ± 4%, FNL = 89.7 ± 3.62% and 93.8 ± 3.17, YsV = 3.3 ± 0.66  μ l 3 and 3.04 ± 0.42  μ l 3 ). Fertilization and hatching rates and quality of larvae showed optimal temperature for successful egg incubation and production of high quality larvae to be 6 to 10°C. Relationship of ontogenic rate to temperature showed development of the pike embryo to be hypothetically stopped at 3.3°C.